2018
DOI: 10.2478/picbe-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

The Globalization in the actual Context of the European Union Economy

Abstract: In this paper, the authors aim to realize an in-depth analysis of the current characteristics of the globalization phenomenon from the viewpoint of the European Union and Romanian economy. The study will pursue some of the globalization indicators published by Eurostat, their status and a multidimensional perspective on their evolution. Namely, the foreign trade, the foreign direct investments, the employment, value added shall be subjected to analysis. The authors will apply statistical and econometric techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
8
1
Order By: Relevance
“…Our results contrast with those reported by Shtasel et al (on patients without medication) who concluded that women had a better quality of life than men, specifically in the social and relationship domains (31). Our findings using the WHO-QoL -BREF score were similar to the results obtained of Yu-Tao Xiang and colleagues who showed that female patients suffering from schizophrenia had a lower quality of life than men who had the same illness (32).…”
Section: Discussioncontrasting
confidence: 61%
“…Our results contrast with those reported by Shtasel et al (on patients without medication) who concluded that women had a better quality of life than men, specifically in the social and relationship domains (31). Our findings using the WHO-QoL -BREF score were similar to the results obtained of Yu-Tao Xiang and colleagues who showed that female patients suffering from schizophrenia had a lower quality of life than men who had the same illness (32).…”
Section: Discussioncontrasting
confidence: 61%
“…A helpful tip is to set the markers along the nerve course (which projects superficially by connecting the mandible angle and the mastoid process), addressing this line in middle. The lower course of this line should be avoided, as it generally represents the assumed path of the spinal accessory nerve (23).…”
Section: Discussionmentioning
confidence: 99%
“…The type IIIC diabetes nomenclature was first proposed in 2014 by the American Diabetes Association, with the name type 3c diabetes now commonly accepted (17)(18)(19). The most widely reported conditions are the presence of chronic pancreatitis (79%), pancreatic ductal adenocarcinomas (8%), haemochromatosis (7%), cystic fibrosis (4%), and previous pancreatic surgery (2%) (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Those patients developing DM are likely to have co-existing pancreatic exocrine insufficiency. The treatment administered on one hand, and the enzymatic insufficiency instituted following chronic pancreatitis on the other hand, contribute to the disease expression and evolution (21). The major risks in all these circumstances are those of severe hypoglycemia characteristic of T3cDM.…”
Section: Discussionmentioning
confidence: 99%